Rapid Determination of Antifibrinolysin (Antiplasmin) in Plasma - Nanninga, L. B; Guest, M. M (Thrombosis and Haemostasis, 1966)
A nephelometric assay of antifibrinolysin in plasma is described. This assay is based on the inhibition of fibrinogenolysis. An equation is derived to calculate the antifibrinolysin content. Only the activity of the rapid acting antifibrinolysin is obtained. The values for antifibrinolysin are given in mol/L based on a molecular weight 57.000 (1). All values are based (standardized) on the inhibition of fibrinolysin by crystalline soybean trypsin inhibitor.